Implementasi Model Pembelajaran Kooperatif Tipe Make A Match dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Fiqih di MTs Annajah - Ulya Safira Ulya; Zaimudin (CV. Ulil Albab Corp, 2023)
This research aims to determine the application of the make-a-match type cooperative learning model in increasing students' interest in learning in fiqh subjects. This research was caused by students' low interest in Fiqh subjects due to the lack of variety in learning models. The advantage of the make-a-match type cooperative learning model is that it is fun. This research uses qualitative research methods with the type of classroom action research. The data collection techniques used are observation and documentation. This research was conducted at MTS Annajah Jakarta with a sample of 28 class VII.3 students. Based on the results of this research, the make-a-match type cooperative learning model can increase students' interest in learning in Fiqh subjects. This can be seen from students’ enthusiasm, expression, and enthusiasm of students when carrying out the make-a-match type cooperative learning model in Fiqh subjects